Associations between occupational performance and quality of life, well-being, and instrumental activities of daily living in older adults/ Associações entre desempenho ocupacional e qualidade de vida, bem-estar e atividades instrumentais da vida diária em idosos - Miki, Emi; Kawabata, Risa (Cadernos Brasileiros de Terapia Ocupacional, 2021)
This study aimed to investigate the associations between occupational performance and quality of life, well-being, and instrumental activities of daily living in older Japanese adults by examining the correlations between the Canadian Occupational Performance Measure and other assessment instruments. We recruited 45 participants (≥65 years old, without dementia) from inpatient and outpatient rehabilitation services in Japan. The associations between the Canadian Occupational Performance Measure as a measure of occupational performance and satisfaction and the Medical Outcomes Study Short Form-36 as a measure of the quality of life, Philadelphia Geriatric Center Morale Scale as a measure of well-being, and Tokyo Metropolitan Institute of Gerontology Index of Competence as a measure of instrumental activities of daily living were examined using Spearman’s correlation coefficient. The Canadian Occupational Performance Measure performance and satisfaction scores showed fair correlations with the physical and mental component summary scores of the Medical Outcomes Study Short Form-36 (r = 0.35 and 0.45, respectively) but not with the role or social component summary scores. Both performance and satisfaction scores showed fair correlations with the total Philadelphia Geriatric Center Morale Scale score (r = 0.35 and 0.41, respectively), but not with the total Tokyo Metropolitan Institute of Gerontology Index of Competence score. The occupational performance showed fair correlations with quality of life and well-being but not with instrumental activities of daily living in older Japanese adults.